NEGATIVE IMPACTS OF PROTAGONIST’S MARITAL INFIDELITY IN S. J. WATSON’S NOVEL BEFORE I GO TO SLEEP - Sofia Idham Nasution; Zulfan Sahri (JOURNAL OF LANGUAGE, 2020)
This study is conducted to analyze the context of marital infidelity from novel Before I Go to Sleep and find out its negative impacts among married couple. The negative impacts which are being analyzed in this study are divorce, illness, loneliness, and emotional trauma. This study uses descriptive qualitative method because the process of the result and discussion are accomplished descriptively. The descriptive qualitative method is applied to explain the negative impacts of marital infidelity from the quotations in the novel. The result of this study is to find the implementation of marital infidelity that is still common among married couple; moreover, the implementation only brings a negative impact to one or both parties. The married couple needs to communicate continually to uncover any problem that appears as the time is passing by in order to avoid specifically divorce, loneliness, and emotional trauma.